2015
DOI: 10.1111/gcb.13099
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions and global warming potential of traditional and diversified tropical rice rotation systems

Abstract: Global rice agriculture will be increasingly challenged by water scarcity, while at the same time changes in demand (e.g. changes in diets or increasing demand for biofuels) will feed back on agricultural practices. These factors are changing traditional cropping patterns from double-rice cropping to the introduction of upland crops in the dry season. For a comprehensive assessment of greenhouse gas (GHG) balances, we measured methane (CH4 )/nitrous oxide (N2 O) emissions and agronomic parameters over 2.5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 47 publications
9
62
1
2
Order By: Relevance
“…Meanwhile, N 2 O emissions were generally higher in optimum soil moisture and N supply as a result of tight coupling between nitrification and denitrification (Snyder et al 2009). Those results were in well agreement with earlier studies (Knox et al 2015;Weller et al 2016) showing that the formation of aerobic conditions caused by land use conversion could result in the reduced CH 4 fluxes at the expense of increasing N 2 O fluxes (Jiang et al 2009). In our study, episodic higher CH 4 emission still occurred in the early conversion days (Fig.…”
Section: Effects Of Land Use Conversion On Soil Ch 4 and N 2 O Fluxessupporting
confidence: 93%
See 4 more Smart Citations
“…Meanwhile, N 2 O emissions were generally higher in optimum soil moisture and N supply as a result of tight coupling between nitrification and denitrification (Snyder et al 2009). Those results were in well agreement with earlier studies (Knox et al 2015;Weller et al 2016) showing that the formation of aerobic conditions caused by land use conversion could result in the reduced CH 4 fluxes at the expense of increasing N 2 O fluxes (Jiang et al 2009). In our study, episodic higher CH 4 emission still occurred in the early conversion days (Fig.…”
Section: Effects Of Land Use Conversion On Soil Ch 4 and N 2 O Fluxessupporting
confidence: 93%
“…In the present study, based on the agricultural practices, some crop residue was typically retained in paddy fields, which led to high level of soil DOC concentration throughout the observing period (Table 2). While in orchard fields, soil DOC contents decreased due to the improved soil aeration and increased mineralization activity (Weller et al 2016). Thus, our result confirmed that higher CH 4 fluxes were observed from paddy soils where DOC contents were higher (Zou et al 2005;Yao et al 2012).…”
Section: Effects Of Land Use Conversion On Soil Ch 4 and N 2 O Fluxessupporting
confidence: 83%
See 3 more Smart Citations